KOREAN WAVE SEBAGAI FENOMENA DIGITAL: STUDI TENTANG RESPON PEMERINTAH İNDONESIA - Inayah, Astiwi; Ramadhan, Jelang; Septiani, Winda; Darmaji, Agung (SOSIOLOGI: Jurnal Ilmiah Kajian Ilmu Sosial dan Budaya, 2024)
South Korea has successfully utilized digital media to promote its popular culture as part of its cultural diplomacy strategy. The popularity of South Korean culture in various countries, including Indonesia, emerged in the Korean wave or Hallyu phenomenon. This shows how cultural globalization can shape international relations and social dynamics in the digital era. This research aimed to analyze how the Indonesian government responds to the spread of the Korean wave and what aspects drive the government's response. This research used the concept of intersubjectivity (inter-subject interaction) in the perspective of constructivism according to Alexander Wendt and a qualitative approach with primary data collection techniques through interviews and secondary data through journals, previous research, archival documentation, and websites. The research was analyzed using six main steps according to Bryman. The results showed that the Indonesian government tends to give a positive and open response to the spread of the Korean wave while still paying attention to the regulations that apply in Indonesia. This response when analyzed using the concept of inter-subject interaction is driven by several aspects such as history, interaction, and interests. The results of the study are expected to provide an understanding of how the Indonesian government responds to the rapid development of foreign cultures while at the same time the government is faced with the challenge of maintaining the existence of local culture and popularizing the culture of its own country.